Preservice Biology Teacher's TPACK Integration into Lesson Planning - Agustina, Putri; Agustina, Lina; Astuti, Rina; Chotimah, Yesi; Ramadhanty, Putri Gayatri; Saputra, Alanindra (Universitas Muhammadiyah Surakarta, 2023)
This research was aimed to investigate preservice Biology teacher’s performance in integration TPACK into lesson plans. The subjects in this study were preservice biology teacher taking Biology lesson planning and microteaching course. The object of this research was all of lesson plan developing by preservice biology teacher. The aspects of TPACK that were examined for integration of TPACK in the lesson plans included content knowledge (CK), pedagogical knowledge (PK), technological knowledge (TK), technological content knowledge (TCK), technological pedagogical knowledge (TPK), pedagogical content knowledge (PCK), and technological pedagogical and content knowledge (TPACK). TPACK integration data on the lesson plan was obtained through documentation techniques and analyzed using an identification sheet. The result of identification were analyzed descriptively using percentage techniques. The results of the identification show that the integration of TPACK aspects into lesson planning at the microteaching course is: learning objectives of 66.67%, opening activities of 30.77%, core activities of 89.74%, closing activities of 7.69%, student worksheet of 38.46%, and assessment instruments of 12.82%. While the integration at the biology lesson planning course is: learning objectives of 78%, opening activities of 33%, core activities of 89%, closing activities of 22%, student worksheet of 51%, and assessment instruments of 13%.